2008
DOI: 10.1002/cb.235
|View full text |Cite
|
Sign up to set email alerts
|

Perceived trustworthiness of online shops

Abstract: Trust has been found to be crucial for consumer behaviour towards online shops. However, existing studies on the role of trust in electronic commerce are mainly based on ad hoc scales to measure trustworthiness, merely rely on self-reported consequences of trust such as intention to buy, and focus on low-risk products. In a web-based study, 634 participants interacted with a provider of medical goods, that is a simulated online pharmacy. The study develops and employs a psychometrically sound scale for assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(112 citation statements)
references
References 61 publications
3
105
0
4
Order By: Relevance
“…Hence, the moderating role of risk perception related to online shopping is an important topic that has not received enough consideration in the literature. Some researchers have studied the moderating effect of risk perception on the link between trust and shopping behavior or intention (Büttner and Göritz, 2008), on the effect of brand image or reputation on the evaluation of a supplier or a product (Gurhan-Canli and Batra, 2004), on the impact of satisfaction on online trust (San Martin and Camarero, 2009), on the predictor of trust (Martin and Camarero, 2009), or on some links of the Technology Acceptance Model (TAM) (Featherman and Fuller, 2002). San Martin and Camarero (2009) reported that "Since the results partly corroborate the theoretical assumptions, it is necessary to keep working in this line and increase the number of papers using perceived risk as a moderating variable.…”
Section: Jssmentioning
confidence: 99%
“…Hence, the moderating role of risk perception related to online shopping is an important topic that has not received enough consideration in the literature. Some researchers have studied the moderating effect of risk perception on the link between trust and shopping behavior or intention (Büttner and Göritz, 2008), on the effect of brand image or reputation on the evaluation of a supplier or a product (Gurhan-Canli and Batra, 2004), on the impact of satisfaction on online trust (San Martin and Camarero, 2009), on the predictor of trust (Martin and Camarero, 2009), or on some links of the Technology Acceptance Model (TAM) (Featherman and Fuller, 2002). San Martin and Camarero (2009) reported that "Since the results partly corroborate the theoretical assumptions, it is necessary to keep working in this line and increase the number of papers using perceived risk as a moderating variable.…”
Section: Jssmentioning
confidence: 99%
“…Bart, et al (2005) show that trust mediates relationships between website design characteristics and purchase intensions; Crosby, Evans and Cowles (1990) show that enhanced trust leads to continued exchanges between parties and to sales; Doney and Cannon (1997) demonstrate that trust influences buyer's anticipated future interactions; Ganesan (1994) shows that trust and interdependence determine the long-term orientation of both retail buyers and their vendors; Geyskens, Steenkamp and Kumar (1998), in a meta-analysis of 24 papers studies (27 studies), suggest that trust mediates roughly 49% of long-term outcomes; Trifts and Häubl (2003) show that the effect of competitive price information is mediated through trust; Hoffman, Novak and Peralta (1999, p. 85) posit that "the most effective way for commercial web providers to develop profitable exchange relationships with online customers is to earn their trust;" and Sirdeshmukn, Singh and Sabol (2002) provide evidence that benevolent management policies and procedures enhance trust and that trust enhances long-term loyalty. Büttner and Göritz (2008) provide evidence that trust enhances intentions to buy.…”
Section: Competitive Information Vulnerability and Trustmentioning
confidence: 95%
“…There is ample precedent in the literature for trust as a mediator of purchase or purchase intentions (e.g., Bart, et al 2005;Büttner and Göritz 2008;Erdem and Swait 2004;Morgan and Hunt 1994;Porter and Donthu 2008;Urban, Amyx, and Lorenzon 2009;Yoon 2002). In a series of experiments, Trifts and Häubl (2003) demonstrate that competitive price information affects preference, but the effect on preference is mediated through trust.…”
Section: Trust As a Mediatormentioning
confidence: 99%
“…Trust is crucial in increasing Internet users' intention to engage in online commercial transactions (Buttner & Goritz, 2008;Everard & Galleta, 2005;Gefen, 2000;Keh & Xie, 2009;Kim, Ferrin, & Rao, 2008) and avail online commercial services (McKnight, Choudhoury, & Kacmar, 2002). Several studies on egovernment have also indicated that trust is an essential ingredient for the acceptance and adoption of online government services (Belanger & Carter, 2008;Carter & Belanger, 2005;Colesca & Dobrica, 2008).…”
Section: Trust As a Catalyst For Disclosure Intention And Risk Percepmentioning
confidence: 99%
“…In fact, a sizable number of empirical studies affirmed that trust is pivotal in influencing Internet users' decision to engage in online commercial exchanges (Buttner & Goritz, 2008;Everard & Galleta, 2005;Gefen, 2000;Keh & Xie, 2009;Kim, Ferrin, & Rao, 2008;McKnight, Choudhoury, & Kacmar, 2002) and noncommercial transactions, such as those done with government organizations (Belanger & Carter, 2008;Carter & Belanger, 2005;Colesca & Dobrica, 2008). Trust also steers Internet users to share their personal information for computer-mediated transactions (Malhotra, Kim, & Agarwal, 2004;McKnight, Choudhoury, & Kacmar, 2002;Schoenbachler & Gordon, 2002;Dinev & Hart, 2006;.…”
Section: Determinants Of Trust In Government Organizations Within Thementioning
confidence: 99%